Saxophone teaching and learning: interdisciplinary relationship music, arts and emotions - López García, Aroa (2018)
: The topic that focused this research was the need of the saxophone students to expand their instrumental and musical knowledge through holistic and interdisciplinary training (cultural, aurally and research) without forgetting the need and importance of motivation through arts.Currently, the results of this didactic experience, which can be observed through the videos of the different class sessions, are being very positive, because these studentshave been aware of the importance of having continuous technical and expressive education with a complete interdisciplinary work including the search of different arts to connect with the emotions to be transmitted, both in the moment of improvisation and the interpretation of the piece or song.